Wind energy resource assessment of desert sites in Algeria: energy and reduction of CO2 emissions - Miloud Benmedjahed; Rachid Maouedj; Samir Mouhadjer (Institute of Advanced Engineering and Science, 2020)
This paper presents a statistical analysis of wind potential of four locations in southern Algeria, namely Adrar, In Salah, Illizi and Tamanrasset, using the Weibull distribution. The evaluation the energy production by the CALORIUS 37 wind turbine taking into account the meteorological (wind and temperature and geographical (latitude, longitude and altitude) datas of these locations. The data were collected every 3 hours over 5 years and used to estimate of the annual energy produced, in order to determine the amount of three types of fossil energy (natural gas, gasoil and gasoline) preserved and the quantities of CO2 that can be avoided. The shape parameter k, varies from 2.0 (Illizi and Tamanrasset) to 2.48 (In Salah), this means that all the distributions are stable, while the scale parameters C varies from 4.6 m/s (Illizi) to 6.3 m/s (In Salah) and mean velocity v varies from 4.1 m/s (Illizi) to 5.5 m/s (Adrar), while the annual energy produced by CALORIUS 37 range from 4467.6 kWh (Illizi) to 8409.6 kWh (Adrar), the equivalent of energies range from 0.38 TEP (Illizi) to 0.72 TEP (Adrar) and the amount of carbon dioxide (CO2 ) that we can provide varies from 0.90 TE-CO2 (natural gas power plant in Illizi ) to 2.24 TE-CO2 (gasoil power plant in Adrar).